Analysis of Cognitive Image, Affective Image and Image Of Uniqueness To The Image of A Tourist Destination Mediated By Digitalization At The Serdang Bedagai Mutiara Beach - Slamet Widodo; Elfitra Desy Surya Andriani; Virdyra Tasril Andriani; M. Agung Putranto Andriani (Sean Institute, 2023)
The purpose of this research is to improve the image of the Pearl Beach destination with digital-based promotions in Pari Serdang City Bedagai and to test and analyze the impact of enhancing the image of the Mutiara Beach destination as a through tour tourist satisfaction with digital-based promotions in Pari Serdang City Begai. The hypothesis in this research is cognitive image, affective image and image unique positive and significant effect simultaneously to enhance the image pearl beach destinations as tourism with digital-based promotions in Kota Pari is different, and cognitive image, affective image and unique image partially positive and significant effect to enhance the image pearl beach destinations as tourism through tourist satisfaction with digital-based promotion of Pari Serdang Bedagai City. The materials to be used in this study are: Quantitative Materials, where the Quantitative Material in this study relates to the data describe variable X1 cognitive image, variable X2 affective image, variable X3 unique image, Y1 (Mediation Variable) tourist satisfaction, and for the variable Y2 is the destination image. The research location was carried out at the pearl beach of Pari City Serdang Bedagai District, North Sumatra Province. Data analysis used are: Quantitative Analysis consisting of Path Analysis (Path Analysis) with a population of 300 consumers and with using the slovin formula obtained a sample of 171 people.